Diagnosis of coronary artery disease by estimation of coronary sinus lactate. Issue 9 (September 1978) - Jackson, G; Atkinson, L; Clark, M; Crook, B; Armstrong, P; Oram, S
Abstract : In an attempt to assess the value of coronary sinus lactate estimation before and during atrial pacing for the diagnosis of obstructive coronary artery disease, 70 patients with angina were investigated in this way and by selective coronary arteriography. Thirty-five had radiologically normal coronary arteries and 35 had coronary artery disease. When the change in coronary arteriovenous lactate difference was less than 0.09 mmol/l (0.8 mg/100 ml) between the control and the peak atrial pacing sample, the coronary arteries were normal except in one patient who had distal disease of a single vessel. When the change was greater than 0.22 mmol/l (2.0 mg/100 ml) coronary artery disease was always found, and when the change was greater than 0.39 mmol/l (3.5 mg/100 ml) there was always disease of two or three vessels. Unfortunately, the presence or absence of coronary artery disease could not be predicted when the change fell between 0.09 and 0.22 mmol/l (0.8 and 2.0 mg/100 ml). Estimation of coronary sinus lactate before and during atrial pacing can thus frequently distinguish patients with normal coronary arteries from those with coronary artery disease.